THE CONCEPT OF SCHOLAR'S HEALTH TERM OF BASIC EDUCATION TEACHERS (Fiep Bulletin - online, 2015)
The concept of health in the school atmosphere bases some practices developed during the process of the child's formation in school age, having  the teachers a great importance  process. Through this research, it tried to investigate the concept of the scholar's health among the educational of the basic education of two different social contexts: public and private schools. The bording of the study is the qualitative type and the technique used to analysis the data was a thematic analysis. The results had shown that such conceptualization  is linked to the practices of health teaching with emphasis in the traditional aspects of hygiene and feeding. The answers obey a lineal logic of cause and effect and they hadn't gotten to express a perspective more including than  it involves the health subject in its several aspects.
Keywords: Scholar's Health; Health Education; Health; Education; Teachers